Dimension of Rural Development in Nepal - Acharya, Bala Ram (Dhaulagiri Journal of Sociology and Anthropology, 2008)
Rural development in Nepal is a complex phenomenon involving an interaction of economic, social, political and cultural factors. The concept of rural development is a process of development and change to improve rural social life entirely. It is linked to infrastructural development, commercialization of agriculture, proper utilization and mobilization of resources, food security, creating opportunities, inclusive social development in the rural community and modernization of overall society. However, achievements of rural development efforts in Nepal are not satisfactory because of imposed development, unstable political situation, absence of people's participation, lack of research and political commitment. Key Words: Rural development, rural poverty, human development in Nepal DOI = 10.3126/dsaj.v2i0.1363 Dhaulagiri Journal of Sociology and Anthropology Vol.2 pp.181-192